THE EFFECT OF LEADERSHIP SKILLS AND TRAINING ON EMPLOYEE PERFORMANCE BY MEDIATION OF INNOVATION CAPACITY IN GLASS MANUFACTURING COMPANIES - Susilo Purnaman; Furtasan Ali Yusuf; Uli Wildan Nuryanto (International Journal of Economy, Education and Entrepreneurship, 2022)
This study investigates the role that innovative capacity plays in the functioning of glass manufacturing businesses. A behavioral approach is taken toward leadership skills, as well as employee training, in the design of the research method. The employees of the production divisions of PT. Fortuna Inti Talenta (140 respondents) and PT. Maruni Daya Sakti makes up the research sample (140 respondents). The results of study 1) leadership has a positive and significant effect on innovation capacity and employee performance (0.002 and 000). 2. Job training positively and significantly affects innovation capacity and employee performance (0.000 and 0.017). Finally, 3) innovation capacity positively and significantly affects employee performance. (0.001). Limitations of the research, the number of participants in this study's sample was lower than the minimum required (560 respondents). As a result, the subsequent researcher will be able to analyze based on the total number of samples from respondents